2011
DOI: 10.1088/0004-637x/744/1/31
|View full text |Cite
|
Sign up to set email alerts
|

On the Injection Spectrum of Relativistic Electrons in High-Redshift Radio Galaxies

Abstract: We point out that the remarkable linearity of the ultra-steep radio spectra of high redshift radio galaxies reflects a previously reported general trend for powerful radio galaxies, according to which the spectral curvature is lesser for sources having steeper spectra (measured near rest-frame 1 GHz). We argue based on existing theoretical and observational evidence that it is premature to conclude that the particle acceleration mechanism in sources having straight, ultra-steep radio spectra gives rise to an u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…However, the k-correction mechanism has been disputed owing to the remarkable linearity and the lack of evidence for a spectral curvature in wide band radio spectrum of high redshift radio galaxies (Chambers et al 1990;Klamer et al 2006Klamer et al , 2007. Gopal-Krishna et al (2012) however argue that since the steepness of the spectral index anti-correlates with the spectral curvature (Mangalam & Gopal-Krishna 1995), the spectral steepening becomes negligible for sources with steep spectra (α 1GHz ≤ −1.2, also reflected in Klamer et al (2006)). k-correction being insufficient to explain the observed z − α relation, alternative effects have been proposed.…”
Section: Hotspot Spectral Indicesmentioning
confidence: 91%
“…However, the k-correction mechanism has been disputed owing to the remarkable linearity and the lack of evidence for a spectral curvature in wide band radio spectrum of high redshift radio galaxies (Chambers et al 1990;Klamer et al 2006Klamer et al , 2007. Gopal-Krishna et al (2012) however argue that since the steepness of the spectral index anti-correlates with the spectral curvature (Mangalam & Gopal-Krishna 1995), the spectral steepening becomes negligible for sources with steep spectra (α 1GHz ≤ −1.2, also reflected in Klamer et al (2006)). k-correction being insufficient to explain the observed z − α relation, alternative effects have been proposed.…”
Section: Hotspot Spectral Indicesmentioning
confidence: 91%
“…The hotspots along with the lobes therefore remain in the high-pressure medium for a prolonged duration. A reduction in the velocity will result in the production of electrons with steeper energy distribution (Kirk & Schneider 1987;Mangalam & Gopal-Krishna 1995;Klamer et al 2006;Gopal-Krishna et al 2012).…”
Section: Pdzα Parameters Of Grgsmentioning
confidence: 99%
“…As a result, the advance of their hot spots is slowed down, giving rise to a steep energy spectrum of the relativistic electrons accelerated there via the firstorder Fermi process, which causes an ultra-steep straight synchrotron radio spectrum ab initio (Athreya & Kapahi 1998;Klamer et al 2006;Bicknell et al 1997). This potentially attractive theoretical scenario would, however, need further substantiation, particularly in view of the empirical study presented by Gopal-Krishna et al (2012), which found no correlation of the particle injection spectral index with rotation measure for powerful double radio sources.…”
Section: Introductionmentioning
confidence: 99%